A Complaint Management System for Enhanced Efficiency at West Visayas State University Himamaylan City Campus - Edlin Z. Muzones; Jake R. Pomperada (Philippine Social Science Journal, 2025)
To address the impact of unresolved complaints on institutional credibility, West Visayas State University – Himamaylan City Campus (WVSU-HCC) developed a secure, web-based Complaint Management System (CMS) to replace inefficient manual processes. This scalable solution streamlines operations through intelligent routing, real-time tracking, automated notifications, and robust analytics, ensuring transparency and accountability. Built on Agile methodology, the platform meets WCAG 2.0 accessibility standards and strict data protection regulations while delivering high availability and rapid response times across devices. The project demonstrated strong economic viability with a projected 750% ROI and achieved high user satisfaction scores for its interface and security features. Ultimately, the CMS successfully automated workflows to reduce resolution times, with future recommendations prioritizing AI integration and cloud migration to ensure sustained scalability.